Event-related potential correlates of consciousness in simple auditory hallucinations - Filimonov, Dmitri; Lenkkeri, Saana; Koivisto, Mika; Revonsuo, Antti (Elsevier BV, 2025)
Neural correlates of consciousness (NCC) have been proposed for perceptual awareness in various sensory modalities. To date, perceptual awareness negativity (PAN) and late positivity (LP) are considered the main NCC candidates, and the question remains which one is the NCC proper. Investigating states where the content of consciousness is independent of the physical stimulus, may provide additional theoretical and empirical value. We studied the event-related potential (ERP) markers of auditory awareness in simple auditory hallucinations using a Pavlovian conditioning paradigm, where participants listened to the near-threshold tones and stimulusabsent trials, rating subjective clarity with the perceptual awareness scale (PAS). The results showed auditory awareness negativity (AAN) - an early event-related potential difference between aware and unaware stimuli - in the hallucinatory condition, suggesting that AAN is an NCC proper in auditory consciousness. Late positivity was absent in simple auditory hallucinations.